Hubungan Penerapan Discharge Planning dengan Tingkat Kepatuhan Pasien Rawat Inap check up di RSUD Karanganyar - Christiana Arin Proborini; Yeni Nur Rahmayanti (Jurnal Stethoscope, 2020)
ABSTRAK Pelaksanaan discharge planning di akhir pasien akan pulang tentunya tidak akan berjalan optimal. Discharge planning dapat dilakukan ketika pasien masuk dan selama proses perawatan, sehingga pasien memahami tindakan yang tepat untuk perawatan dirinya. Hasil studi pendahuluan masih adanya jumlah pasien yang dirawat inap di RSUD Karanganyar tidak datang kembali untuk kontrol. Discharge planning merupakan bagian penting dari program perawatan klien yang dimulai segera setelah klien masuk rumah sakit sampai dengan pasien pulang dari rumah sakit.Tujuan dari penelitian ini adalah menganalisis hubungan penerapan discharge planning dengan tingkat kepatuhan  pasien rawat inap untuk kontrol di RSUD Karanganyar. Rancangan penelitian yang digunakan adalah observasional analitik dengan menggunakan studi secara cross sectional. Jumlah sampel penelitian ini menggunakan rumus Slovin diperoleh sampel sebanyak 81. Instrumen menggunakan data rekam medis pasien.Uji statistik menggunakan Uji Chi Square.Hasil analisis menunjukkan adanya discharge planning dengan tingkat kepatuhan pasien rawat inap untuk kontrol di RSUD Karanganyar, diperoleh (p value = 0.378). Kesimpulan dari penelitian ini tidak ada hubungan signifikan antara data discharge planning dengan tingkat kepatuhan pasien rawat inap untuk kontrol di RSUD Karanganyar.  Kata Kunci : Discharge Planning, Kepatuhan Pasien, Rawat Inap                The Relationship between the Implementation of Discharge Planning and the Level of Compliance for Inpatients at check-ups at Karanganyar District Hospital Christiana Arin Proborini1,Yeni Nur Rahmayanti 2  1 STIKes Mitra Husada Karanganyar. Email:christianaarin123@yahoo.com2 STIKes Mitra Husada, Email: yeninur2004@gmail.com      ABSTRACT Discharge planning at the end of the patient's going home certainly will not run optimally. Discharge planning can be done when the patient enters and during the treatment process, so that the patient understands the right course of action for himself The results of the preliminary study still show that the number of patients hospitalized at Karanganyar District Hospital did not come back for control. Discharge planning is an important part of the client care program that starts immediately after the client is admitted to the hospital until the patient is discharged from the hospital. The purpose of this study is to analyze the relationship between the application of discharge planning and the level of compliance of inpatients for control at Karanganyar District Hospital. The research design used was observational analytic study using cross sectional study. The number of samples of this study using the Slovin formula obtained a sample of 81. The instrument used patient medical record data. Statistical tests using the Chi Square Test. The results of the analysis showed a discharge planning with the level of compliance of inpatients for control in Karanganyar District Hospital, obtained (p value = 0.378 ). The conclusion from this study there is no significant relationship between data discharge planning and the level of compliance of inpatients for control in Karanganyar District Hospital.  Keywords: Discharge Planning, Patient Compliance, Inpatient